Radiological findings in individuals at high risk of psychosis - Borgwardt, S J; Radue, E-W; Götz, K; Aston, J; Drewe, M; Gschwandtner, U; Haller, S; Pflüger, M; Stieglitz, R-D; McGuire, P K; Riecher-Rössler, A (Journal of neurology, neurosurgery and psychiatry, 2006)
Objective: To assess the prevalence of radiological magnetic resonance imaging (MRI) findings in individuals at high risk of schizophrenia. Methods: MRI scans from individuals at high risk of schizophrenia (HR; n = 37) were assessed by a radiologist blind to group status and compared with scans from patients with first episode psychosis (FE; n = 30), depressive controls (DC; n = 17), and healthy controls (HC; n = 26). Results: There was a significantly higher proportion of radiological findings in individuals at high risk of schizophrenia (35%) and patients with first-episode psychosis (40%) than in patients with depression (18%) or healthy controls (12%). These differences were specific to findings regarded as potentially clinically significant as opposed to normal variants; however, there was no indication for medical treatment. Conclusions: The results suggest that a large proportion of those at high risk of psychosis have radiological findings on MRI scanning, and that the prevalence of radiological findings in this group is similar to that in patients with first episode psychosis.